2020
DOI: 10.3168/jds.2020-18584
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate and monensin supplementation to postweaning heifer diets: Effects on growth performance, nutrient digestibility, and health

Abstract: The objective of this study was to evaluate growth and performance of postweaning heifers supplemented with monensin (MON), sodium butyrate (SB), or the combination of MON and SB (MSB) compared with heifers not receiving these feed additives. Forty Holstein heifers [mean age 84.2 ± 1.2 d; body weight (BW) 99.8 ± 10.8 kg (mean ± SD)] were housed in a freestall barn, blocked by birth date, and randomly assigned to 1 of 4 treatments in a randomized complete block design. Treatments were (1) 100 g of soybean meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(91 reference statements)
2
2
0
Order By: Relevance
“…However, nutrient digestibility in this study was not affected by dietary BHBA. Similar to our results, sodium butyrate supplementation did not affect the nutrient digestibility in post-weaned heifers ( Rice et al., 2019 ; Stahl et al., 2020 ). The lack of BHBA effect on digestibility could be due to the weaning of goats and the introduction of the solid diet, which is helpful for rumen development ( Kim et al., 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, nutrient digestibility in this study was not affected by dietary BHBA. Similar to our results, sodium butyrate supplementation did not affect the nutrient digestibility in post-weaned heifers ( Rice et al., 2019 ; Stahl et al., 2020 ). The lack of BHBA effect on digestibility could be due to the weaning of goats and the introduction of the solid diet, which is helpful for rumen development ( Kim et al., 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the interaction effects of BHBA supplementation and age on the body weight, average daily gain, and starter feed intake indicated that both the age and dietary BHBA supplementation are vital in the growth and development of goats. The positive effects of BHBA supplementation agree with previous studies on the butyrate supplementation ( Kotunia et al., 2004 ; Mazzoni et al., 2008 ), which was reported to stimulate growth performance and feed intake in lambs ( Cavini et al., 2015 ; Chai et al., 2017 ), calves ( Guilloteau et al., 2009 ), post-weaned heifers ( Stahl et al., 2020 ), pre-weaned pigs ( Mazzoni et al., 2008 ), and growing-finishing pigs ( Sun et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has shown that calves fed starter mixtures with MSB had fewer incidents of diarrhea, greater solid fecal consistency, and fewer electrolyte treatments prior to weaning (Górka et al, 2011a), none of which were observed in the present studies. A recent publication by Rice et al (2019) and Stahl et al (2020) observed that supplementing calves with sodium butyrate decreased the coccidia count in feces. In both of our studies, calves received an oral coccidiostat on d 15 of the study as a preventative measure, which could have diminished or eliminated the MSB response on fecal score and number of incidences of diarrhea.…”
Section: Effect Of Msb Supplementationmentioning
confidence: 98%
“…It is postulated that such favorable outcomes may be attributed to the flavonoids' potential to mitigate the oxidative stress response in kids, ameliorate intestinal injury, and foster the growth and development of the intestines [8]. The improvement effect of monensin on the growth performance of ruminants has been studied for a long time [74][75][76][77], and the similar effect of AGF and monensin in improving kid growth performance has been observed to be comparable. In the current study, a notable upsurge in daily weight gain was documented for the MN group in comparison to the CON group.…”
Section: Discussionmentioning
confidence: 99%